EXPLORING DESTINATION IMAGE AND PROMOTIONAL ACTIVITIES OF SERBIA – VISITORS’ PERSPECTIVE - Labović, Marija; Šagovnović, Ivana (The Business of Tourism, 2024)
The well-established literature emphasized the significant role that destination image plays in shaping tourists’ travel behavior and the potential benefits that can be derived for both the tourist destination and the entire country. Thus, the main goal of this research was to explore how foreign and domestic tourists perceive Serbia’s cognitive, conative, and overall images, as well as the effectiveness of its promotional efforts. The survey research was conducted in the major destinations of Serbia, and it involved a total of 956 tourists. The findings revealed significant differences between the two tourist segments and shed light on lesser-perceived aspects of the destination image, highlighting areas that require attention in the future. The paper offers valuable implications that can address the identified issues effectively.